Incidence of Crime Under the Influence of Alcohol Intoxication in Lahore - Shagufta Shafi; Muhammad Yousaf; Rizwan Zafar Ansari; Anwar UI Haq; Zahid Hussain Khalil; Riaz Gul (Gandhara University, 2018)
OBJECTIVE: To determine the crimes committed under the influence of alcohol in district Lahore. METHODOLOGY: A six months study of alcohol intoxication through cases brought for examination at office of surgeon medicolegal Lahore from January 01, 2016 to June 30, 2016 is conducted. Available data is analysed on SPSS 13 which includes variables of age, gender, socio-economic conditions, religious background, and time of the day when the case brought for examination. RESULTS: Maximum number of cases is of 3rd decade of life i.e. 21-30 year of age. Consumption of alcohol is found highest in younger age group (21-30 years) i.e. 57.6%, while minimum consumption is observed i.e. 4% and 4.1% respectively in the age group of 51-60 years and 61-70 years. The cases which were males, Muslims and brought at day time, formed a larger group which outnumbered the females, non- Muslims and night cases. CONCLUSION: The study indicated that rate of crime incidence under alcohol consumption was significantly high in Muslim males. The facts highlighted by the study are significant and may be helpful to policy makers and law enforcing authorities in the city of Lahore for the years to come.